Sex and Age Differences in Glucocorticoid Signaling After an Aversive Experience in Mice - Yun Li; Bin Zhang; Youhua Yang; Ping Su; James Nicholas Samsom; Albert H. C. Wong; Fang Liu (Cells)
Background: glucocorticoids may play an important role in the formation of fear memory, which is relevant to the neurobiology of post-traumatic stress disorder (PTSD). In our previous study, we showed the glucocorticoid receptor (GR) forms a protein complex with FKBP51, which prevents translocation of GR into the nucleus to affect gene expression; this complex is elevated in PTSD patients and by fear-conditioned learning in mice, and disrupting this complex blocks the storage and retrieval of fear-conditioned memories. The timing of release of glucocorticoid relative to the formation of a traumatic memory could be important in this process, and remains poorly understood. Methods and Results: we mapped serum corticosterone over time after fear conditioning in cardiac blood samples from male and female mice, as well as adult and aged mice using ELISA. We show a significant alteration in serum corticosterone after conditioning; notably, levels spike after 30 min but drop lower than unconditioned controls after 24 h. We further investigate the effect of glucocorticoid on GR phosphorylation and localization in HEK 293T cells by Western blot. Hydrocortisone treatment promotes phosphorylation and nuclear translocation of GR. Conclusions: these data contribute to our understanding of the processes linking stress responses to molecular signals and fear memory, which is relevant to understanding the shared mechanisms related to PTSD.